Alveolar Bone Plate Measurements of Maxillary Anterior Teeth: A Cone Beam Computed Tomography Study - Saba, Madiha; Khan, Saad; Rizvi, Syeda Sameen Zahra; Parveen, Wajeeha; Sherazi, Surriya; Khattak, Seema (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the crest height and facial alveolar bone thickness of the maxillary anterior teeth within the aesthetic zone among dentate adults in Pakistan. Study Design: Cross-sectional Analytical study. Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from Sep 2024 to Feb 2025. Methodology: The assessment of alveolar bone thickness was done in 43 patients with use of cone beam computed tomography (CBCT). The thickness of the alveolar bone facial plate was determined for each tooth type (at three different points i.e., A, B, and C) using a CBCT image and an integrated digital caliper. The analysis included bilateral upper canines (UC), upper lateral incisors (UL), and upper central incisors (UCI). Comparative analysis at 0.05 significance level was done using SPSS software (version 20). Results: Out of the 258 teeth measured, 86 were canines, 86 were lateral incisors and 86 were central incisors. The mean thickness of the alveolar bone facial plates in upper anterior teeth was 1.04±0.09 mm for the lateral incisors, 1.29±0.04 mm for the canines, and 0.98±0.04 mm for the central incisors. These values differed significantly (p<0.001). No significant correlation was observed between age and facial bone plate thickness (p>0.05). Conclusion: There were significant differences in alveolar bone thickness in maxillary anterior region among Pakistani population. Facial plate thickness is an essential factor in determining optimal strategies for early implant placement in the aesthetic zone.